2020
DOI: 10.3390/app10155094
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Changes Influencing the Magnetoresistive Behavior of Bulk Nanocrystalline Materials

Abstract: Bulk nanocrystalline materials of small and medium ferromagnetic content were produced using severe plastic deformation by high-pressure torsion at room temperature. Giant magnetoresistive behavior was found for as-deformed materials, which was further improved by adjusting the microstructure with thermal treatments. The adequate range of annealing temperatures was assessed with in-situ synchrotron diffraction measurements. Thermally treated Cu–Co materials show larger giant magnetoresistance after annealing f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Similar phase separation processes have already been observed in the Co-Cu system and have been attributed to spinodal decomposition [30]. The same seperation process could be responsible for the improved magnetoresistive behavior of annealed Cu-Co HPT-materials [31]. In the 600°C annealed sample, a demixed state is present with the highest coercivity and the smallest magnetic ξ 2 .…”
Section: Magnetic Force Microscopysupporting
confidence: 72%
“…Similar phase separation processes have already been observed in the Co-Cu system and have been attributed to spinodal decomposition [30]. The same seperation process could be responsible for the improved magnetoresistive behavior of annealed Cu-Co HPT-materials [31]. In the 600°C annealed sample, a demixed state is present with the highest coercivity and the smallest magnetic ξ 2 .…”
Section: Magnetic Force Microscopysupporting
confidence: 72%
“…2. Measurements were started after settling the target temperature for 15 min, since similarly processed Co-Cu samples showed the majority of microstructural changes happening only during a short time period after reaching the target temperature [7]. The time stamps of the measurements are represented by the black diamonds in fig.…”
Section: Resultsmentioning
confidence: 99%
“…For RT resistivity measurements within a magnetic field, the experimental setup described in [8,9] was used. Herein, GMR is represented by the difference in resistivity at zero field and highest field in relation to the resistivity at zero field.…”
Section: Methodsmentioning
confidence: 99%
“…IOP Publishing doi:10.1088/1757-899X/1249/1/012047 2 Typical methods to fabricate granular alloys are mechanical alloying, ion implantation, melt spinning and co-evaporation. It was already demonstrated that materials processed by high-pressure torsion (HPT), a severe plastic deformation technique, also show a GMR effect [7][8][9]. Fathoming the prospects of HPT together with a proper concatenation of annealing treatments, this work focuses on the granular GMR effect of a variety of ternary Cu-based materials.…”
Section: Introductionmentioning
confidence: 99%